SUMBER PEMBIAYAAN DAN PRODUKSI BENIH KENTANG DI KECAMATAN KERTASARI KABUPATEN BANDUNG - Amelia Hendra; Eliana Wulandari (Universitas Galuh Ciamis, 2020)
Potato (Solanum tuberosum L.) is one of the sought-after horticultural commodities and has a high economic value. Potato production in Indonesia is still relatively low compared to potato production in other countries. One obstacle in producing potato is the use of sufficiently high capital in potato seed production activities. Kertasari Subdistrict is one of the areas of potato seed production in West Java, especially in Bandung District. Capital constraints have caused farmers have to look for sources of financing that can meet their needs in order to continuously produce potato seeds. Some farmers rely on formal and non-formal financing sources while some others are able to meet capital needs with personal costs. The purpose of this research is to identify funding sources and potato seeds produced by farmers in Kertasari Subdistrict, Bandung District. This research uses a quantitative research design using a descriptive approach. Data analysis tools used are descriptive analysis using cross tabulation analysis. The results showed that farmers who produced potato seeds in Kertasari Subdistrict, Bandung District with funding sources from commercial banks, relatives or neighbors, and private funds had higher production yields compared to farmers without funding from these sources. Whereas farmers without funding from farmer groups, buyers, and agricultural kiosks, had higher production yields compared to farmers who had funding from these sources.